Multiomic features associated with mucosal healing and inflammation in paediatric Crohn's disease. Issue 9 (14th September 2020) - Taylor, Henry; Serrano‐Contreras, Jose Ivan; McDonald, Julie A. K.; Epstein, Jenny; Fell, JM; Seoane, Rocio C.; Li, Jia V.; Marchesi, Julian R.; Hart, Ailsa L.
Summary: Background: The gastrointestinal microbiota has an important role in mucosal immune homoeostasis and may contribute to maintaining mucosal healing in Crohn's disease (CD). Aim: To identify changes in the microbiota, metabolome and protease activity associated with mucosal healing in established paediatric CD Methods: Twenty‐five participants aged 3‐18 years with CD, disease duration of over 6 months, and maintenance treatment with biological therapy were recruited. They were divided into a low calprotectin group (faecal calprotectin <100 μg/g, "mucosal healing, " n = 11), and a high calprotectin group (faecal calprotectin >100 μg/g, "mucosal inflammation, " n = 11). 16S gene‐based metataxonomics, 1 H‐NMR spectroscopy‐based metabolic profiling and protease activity assays were performed on stool samples. Results: Relative abundance of Dialister species was six‐times greater in the low calprotectin group ( q = 0.00999). Alpha and beta diversity, total protease activity and inferred metagenomic profiles did not differ between groups. Pentanoate (valerate) and lysine were principal discriminators in a machine‐learning model which differentiated high and low calprotectin samples using NMR spectra ( R 2 0.87, Q 2 0.41). Mean relative concentration of pentanoate was 1.35‐times greater in the low calprotectin group (95% CI 1.03‐1.68, P = 0.036) and was positively correlated with Dialister . Mean relative concentration of lysine was 1.54‐times greater in the high calprotectin group (95% CI 1.05‐2.03, P = 0.028). Conclusions: This multiomic study identified an increase in Dialister species and pentanoate, and a decrease in lysine, in patients with "mucosal healing." It supports further investigation of these as potential novel therapeutic targets in CD.